Cardiac corin and atrial natriuretic peptide regulate liver glycogen metabolism and glucose homeostasis - Wenguo Li; Xianrui Zhang; Zibin Zhou; Wenjun Guo; Mengting Wang; Tiantian Zhou; Meng Liu; Qingyu Wu; Ningzheng Dong (Cardiovascular Diabetology, 2024)
Abstract Background Cardiovascular function and metabolic homeostasis are closely linked, but the underlying mechanisms are not fully understood. Corin is a protease that activates atrial natriuretic peptide (ANP), an essential hormone for normal blood pressure and cardiac function. The goal of this study is to investigate a potential corin and ANP function in regulating liver glycogen metabolism and glucose homeostasis. Methods Liver glycogen and blood glucose levels were analyzed in Corin or Nppa (encoding ANP) knockout (KO) mice. ANP signaling was examined in livers from Corin and Nppa KO mice and in cultured human and mouse hepatocytes by western blotting. Results We found that Corin and Nppa KO mice had reduced liver glycogen contents and increased blood glucose levels. By analyzing conditional KO mice lacking either cardiac or renal Corin, we showed that cardiac corin and ANP act in an endocrine manner to enhance cGMP-protein kinase G (PKG)-AKT-GSK3 signaling in hepatocytes. In cultured hepatocytes, ANP treatment stimulated PKG signaling, glucose uptake, and glycogen production, which could be blocked by small molecule PKG and AKT inhibitors. Conclusions Our results indicate that corin and ANP are important regulators in liver glycogen metabolism and glucose homeostasis, suggesting that defects in the corin and ANP pathway may contribute to both cardiovascular and metabolic diseases.